2003
DOI: 10.1046/j.1365-2222.2003.01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of seasonal variability in bronchial hyper‐responsiveness and sputum cell counts in non‐asthmatic subjects with rhinitis and effect of specific immunotherapy

Abstract: Bronchial hyper-responsiveness (BHR) is documented in a proportion of non-asthmatic individuals with allergic rhinitis (NAAR) and reflects inflammatory events in the lower airways. Natural exposure to allergens is known to modulate BHR and the level of airway inflammation in asthma, but less consistently in NAAR. Specific immunotherapy (SIT) attenuates symptoms possibly by reducing BHR and airway inflammation. The influence of natural exposure to Parietaria pollen on BHR and sputum cell counts of NAAR was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…Adenosine-induced bronchoconstriction has been shown to be a sensitive marker of airway inflammation by promoting the release of a variety of inflammatory mediators [41], correlating with both exhaled nitric oxide and sputum, blood and bronchial tissue eosinophilia [42] and appears to be better suited to assess the anti-inflammatory effects of ICS than methacholine [43,44]. In the present study, the room for Base PLA CIC320 CIC640 FP500 FP1000 PC20 methacholine mg·mL -1 FIGURE 5.…”
Section: Discussionmentioning
confidence: 68%
“…Adenosine-induced bronchoconstriction has been shown to be a sensitive marker of airway inflammation by promoting the release of a variety of inflammatory mediators [41], correlating with both exhaled nitric oxide and sputum, blood and bronchial tissue eosinophilia [42] and appears to be better suited to assess the anti-inflammatory effects of ICS than methacholine [43,44]. In the present study, the room for Base PLA CIC320 CIC640 FP500 FP1000 PC20 methacholine mg·mL -1 FIGURE 5.…”
Section: Discussionmentioning
confidence: 68%
“…Clinical efficacy (reduction of symptoms and/or need for medications) has been confirmed with grass (1102,1104,(1650)(1651)(1652)(1653)(1654)(1655), birch (1650,1651,(1656)(1657)(1658)(1659), ragweed (1660), Russian thistle (1661), Parietaria pollen (1662,1663), mites (1664)(1665)(1666)(1667)(1668)(1669) and cat (1670). It should be noted that three of the studies (1104,1660,1670) clearly demonstrated that the clinical effect is dose dependent.…”
Section: Aria: 2008 Updatementioning
confidence: 88%
“…Nevertheless, these differences did not reach the statistical significance. Patients were considered to be mono- (17). This may underestimate the actual bronchial hyperresponsivness in this subgroup.…”
Section: Methodsmentioning
confidence: 99%